Pengaruh Esg Disclosure dan Faktor Internal Perusahaan terhadap Nilai Perusahaan di ISSI Periode 2019-2024 - Zaky Fahrezi; RR. Tini Anggraeni (Tauhidinomics: Journal of Islamic Banking and Economics, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure, Return On Asset (ROA), Return On Equity (ROE), Current Ratio (CR), and Price Earning Ratio (PER) on the value of energy sector companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2019–2024 period. The study uses panel data regression method with a Fixed Effect Model (FEM) approach. The results show that simultaneously all independent variables have a significant effect on company value with a Prob F-statistic value of 0.00000 < 0.05 and an adjusted R² of 98.5%. Partially, ROE and CR have a positive significant effect, while ESG, ROA, and PER have a negative effect on company value. These results indicate that investors pay more attention to the management of capital and liquidity of the company rather than ESG disclosure, asset profitability, and PER in making investment decisions.